Wildlife, forests, and forestry : principles of managing forests for biological diversity - Hunter, Malcolm L. (Prentice Hall, 2011)
Wildlife, Forests, and Forestry: Principles of Managing Forests for Biological Diversity furnishes the reader with a conceptual focus and a broad geographic scope of the interface between forestry and wildlife. The universal information contained in the book allows students to understand the concepts that form the foundations for specific management decision making.